Multiplex Sequence Analysis Demonstrates the Competitive Growth Advantage of the A-to-G Mutants of Clarithromycin-Resistant Helicobacter pylori - Wang, Ge (American Society for Microbiology, 1999)
Clarithromycin resistance in Helicobacter pylori is due to point mutation within the 23S rRNA. We examined the growth rates of different types of site-directed mutants and demonstrated quantitatively the competitive growth advantage of A-to-G mutants over other types of mutants by a multiplex sequencing assay. The results provide a rational explanation of why A-to-G mutants are predominantly observed among clarithromycin-resistant clinical isolates.